The AU/NEPAD Peace and Security Governance in Africa - Isaac Terungwa Terwase; Asmat Nizam Abdul Talib; Nfor Eric Siben; Gloria Samdi Puldu; Olubukola S. Adesina (Otoritas : Jurnal Ilmu Pemerintahan, 2017)
Peace and security sustainability in Africa has become a vital tool for the developmental agenda of the Africa Union. Hence, the continent’s conflicting issues and fighting against various groups that emerged from militancy, insurgency and terrorism in Africa is the reason why the peace and security department of the African Union was established for the purpose of solving such problems in order to sustain a peaceful African environment. The main objective of the paper is to draw the role of the African Union (AU) and the New Partnership for Africa’s Development (NEPAD) in assisting the African countries in resolving the conflicts which could lead to a state of insecurity. The work made use of qualitative research design through the conduct of interviews as well as the use of other sources such as AU/NEPAD documents, internet sources and journals for the purpose of data collection. The findings revealed that, NEPAD works with the African countries at the country level through the provision of advisory and partnership role on peace and security governance. At the continental level, NEPAD report to the African Union on issues relating to peace and security sustainability which are handled by the AU’s department for Peace and Security.